Use of Shape Memory Alloys as Smart Materials to Harvest Energy Powered by Renewable Energy Resources - (:unkn) unknown (IEEE, 2017)
This paper will study heat engines driven by smart metals also named as Shape Memory Alloys (SMA). It presents studies on contribution to energy production by heat engines driven by SMA using underground thermal water, secondary heat resources of combined cycle natural gas power plants and renewable energy resources. It also studies SMA heat engines with regards to energy conversion.
Keywords: Smart materials; Shape memory alloys; Heat engines; Renewable energy sources; ROTARY ACTUATOR; SYSTEM; WIRES